Optimization of the Number of Cylinder Blades in Coffee Pulper Machine: Finite Element Analysis and Simple Additive Weighting Methods - Syahriza, Mochamad Rifki; Djumhariyanto, Dwi; Ilminnafik, Nasrul; Darsin, Mahros; Yudistiro, Danang; Basuki, Hari Arbiantara; Wibowo, Robertoes Koekoeh Koentjoro; Syuhri, Ahmad; Sumarji, Sumarji (Universitas Negeri Malang, 2024)
The increasing interest in coffee in all circles means that coffee production and quality must always increase due to consumer demands. One way to maintain the quality of coffee beans is by breaking them down using a huller machine. This research aims to improve the optimization of coffee machines by modifying the cylinder blades of huller machines with variations of 3, 4, 5, and 7 cylinder blades in terms of static loading design and quality and production capacity of coffee bean breaking. The experiment was carried out using 400 rpm and breaking 10kg of dry coffee cherries every time the sample was taken. The research results show that the best sample collection is the variation of 3 cylindrical blades with the maximum stress and lowest deformation values of 6.67 MPa and 0.000737 mm. In terms of production quality, it shows that the best sampling was the three cylindrical blade variations with 50% whole and good coffee beans. In terms of production capacity, the most significant capacity was the seven cylindrical blade variations with a value of 294.11 kg/hour. Sampling from the four most optimal variations uses the SAW (Sample Additive Weighting) method. The most optimal result from the 4 test criteria, the variation of 3 cylindrical blades is the best because it has the highest score with a value of 0.9754.